2017
DOI: 10.1111/crj.12685
|View full text |Cite
|
Sign up to set email alerts
|

How is chronic non‐communicable respiratory conditions research reported in European newspapers? An impact assessment for policy

Abstract: Background: Newspapers are an important means for the communication of medical research findings to policy-makers and the public, but may distort their views on the relative importance of research into, and burden from, different respiratory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…The clinical importance of such a shift in the trend of the cited research evidence-base for clinical practice may be due to a potential shift towards new or experimental treatments tackling COPD. Although this cannot be inferred in this study, a previous study demonstrated that the citation of asthma research in European CPGs was more clinical than COPD [7] while research reported on newspaper stories was more basic than that of COPD [8]. Also, the latter study [8] demonstrated a heavily reporting research on asthma than COPD despite the reverse image presented by the disease burden afflicted by the European population.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The clinical importance of such a shift in the trend of the cited research evidence-base for clinical practice may be due to a potential shift towards new or experimental treatments tackling COPD. Although this cannot be inferred in this study, a previous study demonstrated that the citation of asthma research in European CPGs was more clinical than COPD [7] while research reported on newspaper stories was more basic than that of COPD [8]. Also, the latter study [8] demonstrated a heavily reporting research on asthma than COPD despite the reverse image presented by the disease burden afflicted by the European population.…”
Section: Discussionmentioning
confidence: 56%
“…Although this cannot be inferred in this study, a previous study demonstrated that the citation of asthma research in European CPGs was more clinical than COPD [7] while research reported on newspaper stories was more basic than that of COPD [8]. Also, the latter study [8] demonstrated a heavily reporting research on asthma than COPD despite the reverse image presented by the disease burden afflicted by the European population. However, with limited funding, such research practices may even lead to further variation between countries' CPG focus and even greater disparities between the different respiratory conditions.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Chronic respiratory disease is one of the world's leading global health system issues [1], [2]. Indeed, asthma, a chronic disease of the respiratory airways, affects more than 300 million people worldwide [3], [4] with a significantly increased incidence in recent decades [5]- [7].…”
Section: Introductionmentioning
confidence: 99%